Blockchain review for battery supply chain monitoring and battery trading. (April 2022) - Antônio Rufino Júnior, Carlos; Sanseverino, Eleonora Riva; Gallo, Pierluigi; Koch, Daniel; Schweiger, Hans-Georg; Zanin, Hudson
Abstract: The use of technologies such as Internet of Things (IoT), data processing and blockchain have allowed companies to serve their customers with better quality, efficiency, reliability and in the shortest possible time. The growing adoption of electric vehicles on the market has increased the demand for batteries that may have numerous manufacturers. Life expectancy is affected on manufacture, but also on operational conditions. A large number of parameters have a role on battery's health and thousands of data need to be evaluated and combined. The present work investigates the scenario of the battery industry in order to implement a blockchain-based platform for the supply chain implementation thus allowing a better control on performance of batteries and environmental impact. To achieve this goal, the authors carried out a systematic review with the following steps: identification of relevant studies, evaluation and summary of similar studies, comparison and extraction of data from the papers. The main motivation of this work is the use of the literature for justifying the use of the blockchain technology to track batteries and for identifying the main challenges in the related markets that can be addressed by this technology. The results of this systematic review show that the development of a blockchain-based platform for battery tracking will allow for greater transparency across the entire supply chain: production, reuse, recycling, disposal. Trasparency and traceability prevent clandestine markets, misuse and release of pollutants. Adressing these topics forsters the successful implemention of electric vehicles in the market. Highlights: Battery tracking can define who owns the battery at the end of its life. Battery tracking protects stakeholders in the battery market from conflicts of interest. Public policies can be proposed based on data entered into a blockchain-based platform. A blockchain-based platform can inhibit the trade in uncertified batteries. A blockchain-based platform can prevent tampering with battery data.